Application of Rumoh Aceh Elements in Office Buildings as Forming Socio-Historical Society (case study: Banda Aceh city center area) - Zahriah Zahriah; Cut Nursaniah; Masdar Djamaluddin; Salsabilla; Raihan C Havilia; Abrar M Yussya (Talenta Publisher, 2026)
The area in a city should display an architectural product that is able to maintain an architectural formation that is worthy of being maintained to be enjoyed by the city community as a transformed socio-cultural symbol, and cannot be separated from the local history. This is part of the hospitality that shows its identity to the community and people who visit the city, one of which is shown through the architectural characteristics of offices which are public service buildings. The characteristic appearance of office architecture can be a concept that distinguishes a city from other cities as an identity that forms the image of the city. The application of this concept in the city of Banda Aceh is shown by applying the architectural elements of rumoh aceh on the appearance of office architecture, but not all office buildings have implemented it. This qualitative research using the observation method of office buildings in the downtown area of ​​Banda Aceh analyzes the typological parameters of the rumoh aceh architecture. The results of the study conclude that offices in the downtown area have not shown an area that has a strong Acehnese identity. Of the fourteen samples of office buildings, there are only seven samples that can be identified with the application of the rumoh aceh elements as a form of building. The application of the rumoh aceh style element in the downtown area in Banda Aceh is carried out with a design that is integrated into the modern architecture of office buildings. Efforts to familiarize the regional identity so that it can play a socio-historical role through the presence of the local identity of rumoh aceh in office buildings for the community have not been achieved, because the appearance of office architecture is still diverse in the area.